OpenFOAM computational fluid dynamic simulations of single-phase flows in an advanced-flow reactor - Nieves-Remacha, Maria Jose; Kukarni, Amok A.; Jensen, Klavs F. (Industrial & Engineering Chemistry Research, 2015)
Computational fluid dynamic (CFD) simulations are carried out for single-Phase flow in an, advanced-flow reactor (AFR) using the open source software OpenFOAM. Excellent agreement of Simulations with experimental pressure drop and residence time distribution (RTD) is obtained. Streamlines, stagnant zones, Velocity profiles, and pressure fields are,obtained at different flow rates ranging from 5 to 100 mL/min. A change in the flow behavior with the presence of recirculation zones is observed with a 40 mL/min flow rate. The extent of the recirculation zones increases with increasing flow rate from 40 to 60 mL/min and is limited further by the presence of a second cylindrical post inside the heart cell, remaining almost constant in the flow rate range of 60-100 mL/min. The RTD is also determined for all flow rates, and a. comparison between different reactor designs (two-post, single-post, and low-flow-reactor-like single-post) is presented. The APR Shows a plug-flow behavior with a small degree of dispersion, which broadens the RTD. Symmetric RTD curves are obtained for the single-post designs, whereas the Gen 1 APR design experiences asymmetry in the RTD at flow rates in the range between 20 and 60 mL/min.